High value products, supermarkets and vertical arrangements in Indonesia - Chowdhury, Shyamal; Gulati, Ashok; Gumbira-Sa’id, E. (2005)
Indonesian economy has experienced some major changes during the last three decades and transformed from a predominantly agricultural economy to one that relies more heavily on its non-agricultural sector. Within agriculture, there has also been a change in the contribution of different sub sectors and high value products have grown relatively rapidly making agriculture more diversified. Similar to the changes in agricultural production, food consumption in Indonesia has shown a pattern of change over the past three decades, from a diet characterized primarily by the staple foods of cereals and cassava, to one that includes a larger share of fruits, fish, meats, dairy products and processed foods. Alongside the change in composition of food demand, newer forms of retail have also come up commonly known as supermarkets. However, the emergence of modern retailing has other consequences that go beyond consumers. It requires deep integration with farmers and can influence the production and transaction costs at farm level. It can also influence the distribution of value among different agents involved in production, intermediation, and retailing. In this paper we pursue three interrelated objectives. First, we review the structural changes that have taken place in Indonesian agriculture for the last three decades and the state of high value products. Second, we examine the driving forces behind the production of high value products and the constraints that limit their production. Third, we review the emergence of supermarkets and the vertical arrangements among farmers, traders/distributors, and supermarkets. We have relied both on primary and secondary data sources. Most of the secondary data has come from government directorates, different ministries and the central bureau of statistics (CBS) of the Government of Indonesia. In cases where secondary information was not readily available, we have also collected primary data. Our findings suggest that during the last three decades, there has been a significant structural change in Indonesian agriculture and the production of high value commodities and products –estate crops, livestock, fisheries, fruits and vegetables, and floriculture – has grown faster than the cereals. However, the extent of diversification towards high value products has remained limited to few regions and to few products within each sub sector. Factors that have contributed most in diversification are the rapid growth in income and accompanied changes in urban consumption in favor of high value products and agricultural mechanization. The economic crisis that was triggered by the currency crisis has had a long negative impact on agriculture sector. Structural changes in Indonesian agriculture have been accompanied by changes in consumption pattern in urban areas in favor of high value products and by a major change in retailing in the form of growth of modern supermarkets. To cater to the demand of changed urban consumption needs, supermarkets have been integrating with farmers through formal and informal contracts. This vertical relationship between farms and supermarkets that has been emerging in Indonesia has been helpful to follow grades and standards, to improve quality, and to reduce transaction costs and information asymmetries. It has also been helpful to reduce price and production risks at farm level and to ensure a higher price for farmers compared to traditional value chain. However, it seems that the participation of small holders in the vertical relationship depends largely on vendors. Within the vertical chain, supermarkets appropriate a monopsony rent. Important policies that can be drawn from this study are the greater emphasize on rural infrastructure, user right of state-owned estate to smallholders, promotion of public-private partnerships, encouragements of vertical arrangements, grades and standards, and bringing up the modern retailing sector under the purview of regulatory oversights." --Authors' Abstract